Dynamic Assessment in the Writing for Academic Contexts Course - Sudiyono; Suharso; Wipsar Siwi Dona Ikasari; Anis Firdatul Rochma; Rahma Fitriana (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
Dynamic assessment as one kind of interactive assessment in education is used to identify student’s skills and potential. This study explored the use of dynamic assessment (DA) in assessing writing skills within the context of the Writing for Academic Contexts course and aimed to measure the impact of feedback on students' writing skills. This quantitative study was conducted at the English Language Education Study Program, Faculty of Language and Arts, Yogyakarta State University, involving 40 students. The data were students’ writing scores before and after the provision of feedback, collected through tasks of writing various essay types such as comparison and contrast, chronological order, and cause and effect. The data were analyzed using a paired-sample t-test. The results suggest that while feedback can significantly enhance scores in certain essay types, it may not consistently improve writing skills across all contexts. The study underscores the importance of dialogical feedback and mediation in facilitating student understanding and improvement. Overall, the findings highlight the complexity of assessing writing skills and advocate for a dynamic and interactive assessment approach that considers individual student needs, fostering a more comprehensive understanding of their writing abilities.